PENGARUH TINGKAT PEMAHAMAN MANFAAT SUNSCREEN TERHADAP PRILAKU PENGGUNAAN SUNSCREEN DIKALANGAN MAHASISWA LAKI-LAKI - Adlina, Marisha; Lusiana, Mitra (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2025)
Abstract : The background of this study is based on the low awareness and understanding of the importance of sunscreen use, especially among men who tend to neglect skin care even though they are in environments with high sun exposure. Hotel management is one of the departments that requires its students to have a clean, neat and attractive appearance because they work in the service sector, so they must appear professional when meeting clients. The study aims to see the influence of understanding the benefits of sunscreen on sunscreen use behavior among male students of the Faculty of Tourism and Hospitality, Padang State University. This study applies a quantitative approach with a correlational research design. Data were obtained using a questionnaire that has been tested for validity and reliability. Data analysis was carried out using the Spearman Rank correlation test with the help of Statistical Package for the Social Sciences (SPSS) software version 25. The findings of the study indicate a very strong and significant relationship between the level of understanding of the benefits of sunscreen and its use behavior (ρ = 0.908; p < 0.001), so the results of the study state that the higher the understanding of men about sunscreen, the more consistent they are in using it. Keywords: Understanding The Benefits Of Sunscreen, Sunscreen Usage Behavior.